Analysis of Personal Hygiene Factors for Garbage Transporting Officers in Ternate City (Public Health Perspective Journal, 2021)
Personal hygiene is an effort to improve the health status of garbage transporting officers so that garbage transporting officers can avoid various diseases caused by garbage. This study aims to analyze the personal hygiene factors for garbage transporting officers in Ternate City, North Maluku Province. The type of research used is Mixed Methods research, which combines quantitative and qualitative research. With a sequential explanatory design. The population of this study was 143 respondents with a quantitative sample of 59 respondents using the random sampling technique. Research subjects include knowledge, work environment, personal protective equipment (PPE), and socio-culture of garbage transporting officers. Collecting data by means of questionnaires, interviews, observation, and documentation. Quantitative data analysis techniques used the Chi-Square test. The results showed that there was no influence of knowledge with personal hygiene for garbage transporting officers, p-value of 0.404 ( 0.05). work environment p-value of 0.223 ( 0.05). There is an effect of using personal protective equipment (PPE) p-value of 0.007 (0.05). The socio-cultural p-value is 0.010 (0.05). Personal protective equipment (PPE) and socio-culture which more influence the personal hygiene of garbage transporting officers in Ternate city, North Maluku Province.